Interspecies Interactions in Relation to Root Distribution Across the Rooting Profile in Wheat-Maize Intercropping Under Different Plant Densities - Wang, Yifan; Qin, Yazhou; Chai, Qiang; Feng, Fuxue; Zhao, Cai; Yu, Aizhong (Frontiers in Plant Science, 2018)
In wheat-maize intercropping systems, the maize is often disadvantageous over the wheat during the co-growth period. It is unknown whether the impaired growth of maize can be recovered through the enhancement of the belowground interspecies interactions. In this study, we (i) determined the mechanism of the belowground interaction in relation to root growth and distribution under different maize plant densities, and (ii) quantified the ‘recovery effect’ of maize after wheat harvest. The three-year (2014–2016) field experiment was conducted at the Oasis Agriculture Research Station of Gansu Agricultural University, Wuwei, Northwest China. Root weight density (RWD), root length density (RLD), and root surface area density (RSAD), were measured in single-cropped maize (M), single-cropped wheat (W), and three intercropping systems (i) wheat-maize intercropping with no root barrier (i.e., complete belowground interaction, IC), (ii) nylon mesh root barrier (partial belowground interaction, IC-PRI), and (iii) plastic sheet root barrier (no belowground interaction, IC-NRI). The intercropped maize was planted at low (45,000 plants ha-1) and high (52,000 plants ha-1) densities. During the wheat/maize co-growth period, the IC treatment increased the RWD, RLD, and RSAD of the intercropped wheat in the 20–100 cm soil depth compared to the IC-PRI and IC-NRI systems; intercropped maize had 53% lower RWD, 81% lower RLD, and 70% lower RSAD than single-cropped maize. After wheat harvest, the intercropped maize recovered the growth with the increase of RWD by 40%, RLD by 44% and RSAD by 11%, compared to the single-cropped maize. Comparisons among the three intercropping systems revealed that the ‘recovery effect’ of the intercropped maize was attributable to complete belowground interspecies interaction by 143%, the compensational effect due to root overlap by 35%, and the compensational effect due to water and nutrient exchange by 80%. The higher maize plant density provided a greater recovery effect due to increased RWD and RLD. Higher maize plant density stimulated greater belowground interspecies interaction that promoted root growth and development, strengthened the recovery effect, and increased crop productivity.